Hydrogen-Bond-Promoted Metal-Free Hydroamination of Alkynes - Bahri, Janet; Tanbouza, Nour; Ollevier, Thierry; Taillefer, Marc; Monnier, Florian (Synlett, 2019)
An original metal-free regio- and stereoselective intermolecular hydroamination of alkynes is described. Various (E)-enamines were obtained from arylacetylenes and aliphatic secondary amines in the presence of ethylene glycol as a solvent. The latter is assumed to play a major role in the mechanism through hydrogen bonding and proton exchange.
Keywords: hydroamination; alkynes; amines; metal-free; enamines; green chemistry